2016
DOI: 10.1007/s00383-016-4010-2
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of rectal mucosal punch biopsy in the diagnosis of Hirschsprung’s disease: a 30-year experience of 954 patients

Abstract: Punch biopsy including the "K-PUNCH" method is considered safe and feasible and is associated with a low rate of complications and inappropriate specimen harvesting among patients of all ages. Comorbidities, including the potential for hemorrhage, should always be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
(55 reference statements)
0
13
0
2
Order By: Relevance
“…The indications for a rectal mucosal biopsy were as follows: the presence of a symptom indicating intestinal obstruction, such as a bilious vomiting, chronic constipation, and abdominal distension; the presence of dilatation of the intestine on radiography; and the obvious or suspected presence of a “caliber change” indicating the transit zone of HD in a contrast enema. Manometry was not performed as a routine examination 26 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The indications for a rectal mucosal biopsy were as follows: the presence of a symptom indicating intestinal obstruction, such as a bilious vomiting, chronic constipation, and abdominal distension; the presence of dilatation of the intestine on radiography; and the obvious or suspected presence of a “caliber change” indicating the transit zone of HD in a contrast enema. Manometry was not performed as a routine examination 26 …”
Section: Methodsmentioning
confidence: 99%
“…Rectal mucosal punch biopsies, including our original “K‐PUNCH” rectal mucosal punch biopsies, have been performed consecutively in our department and branch hospital 24,26 . Two to four biopsy specimens per patient were obtained, and an AChE histochemistry and HE staining was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The "K-punch," a safe and feasible punch biopsy technique that uses rigid sigmoidoscopy, allows for visualization of the biopsy site and direct grasping sensation. 7 In another study, Ali et al 8 compared the adequacy of specimen size with standard RSB versus wall-suction or machine-suction RSB and found that 81.0% of the standard group had adequate samples when compared with 100% of the wall-suction or machine-suction RSB group (P Z .02). Also, there were no adverse events.…”
mentioning
confidence: 99%